Faktor - Faktor yang Mempengaruhi Minat Beli Konsumen Terhadap Produk Mixue di Kota Pontianak - Machmuda, Dian Nurul; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to identify the factors influencing consumers' purchase intention toward Mixue products in Pontianak City. A descriptive qualitative approach was employed, using data collection techniques including in-depth interviews, observations, and documentation involving ten Mixue consumers. Data analysis was conducted using the Miles and Huberman model, which includes three stages: data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation, allowing verification from multiple perspectives and methods. The findings reveal that consumer purchase intention is influenced by four main factors: affordable pricing, product quality (in terms of variety and taste), quality of service, and store location comfort. These factors collectively contribute to a positive consumer experience and enhance customer loyalty. The study recommends that Mixue maintain its competitive advantage in pricing and flavor while continuing to improve service quality and store ambiance as key strategies in facing intense market competition.